Characterization of ballpoint pen ink using VSC - Amir, Muhammad Aidell (Pusat Pengajian Kesihatan, 2015)
Inks analysis is one of the main focuses in forensic document examination. The ability to differentiate one kind of ink from another can be quite useful in many cases such as document alteration. Many kind of technique has been developed in order to produces an excellent result in differentiating similar colour inks. This research will be focus on the ink discrimination by non-destructive method which includes optical examination under visible light source and ultraviolet (UV) and micro-spectrometry by using Video Spectral Comparator (VSC) 6000. Discrimination power (DP) was used to improve quality of VSC in differentiating visual of similar colour inks. The characteristic of ink was able to discriminate similar colour ink which is blue from different brands by means of differences in spectra. The spectra were compared and DP of 93.33% was obtained. The spectra of ink from different individual ballpoint pen of the same model and brand were similar in their overall pattern. Their physical appearance shows some similar properties between same brands as well as different kind of brands in the microscopic examination. Despite that, similar colour ink is hard to be differentiating under UV light because all of these pens do not fluoresce. As a conclusion, for non-destructive method, VSC would be most preferable technique, not only because it is easy to handle, it is also time efficient.